Determining the Prevalence of Nasal Community-acquired MRSA Carriage and Associated Risk Factors in the Turkish Cypriot Population - Sanliturk, Gizem; Guran, Mumtaz (Bilimsel Tip Yayinevi, 2020)
Introduction: No studies have investigated Community-Acquired Methicillin-Resistant Staphylococcus aureus (CA-MRSA) nasal carriage rate in the Turkish Cypriot community up to now. The aim of this study was to investigate (i) The prevalence of CA-MRSA nasal carriage in the Turkish Cypriot community, (ii) The association of previously identified risk factors with CA-MRSA. Materials and Methods: Our study is a cross-sectional study conducted in Northern Cyprus in 2019 with 487 randomly selected and voluntary participants. In this study, a questionnaire was distributed, and the relationship between nasal CA-MRSA carriage and risk factors was investigated. In addition, the presence of CA-MRSA was determined by taking a nasal swab sample. Results: In this study, the prevalence of nasal CA-MRSA carriage in the Turkish Cypriot society was 6.98% (34/487). Marital status was found to be the only significant risk factor associated with CA-MRSA carriage (p=0.035) in the study. However, it was found that individuals exposed to risk factors of hospitalization during the previous year and using antibiotic during the last year were 1.6 and 3.25 times higher than those who did not, respectively. Conclusion: In this study, marital status was the only statistically significant risk factor associated with CA-MRSA carriage. Furthermore, the prevalence of nasal CA-MRSA carriage in the Turkish Cypriot population was found to be higher than developed countries. In this context, it is essential to develop health strategies for the sustainability of TK-MRSA carriage surveillance and to reduce carriage.
Keywords: CA-MRSA; Nasal carriage; Risk factors; Turkish Cypriot